2021
DOI: 10.5114/aoms.2019.85737
|View full text |Cite
|
Sign up to set email alerts
|

Training in intraoperative neuromonitoring of recurrent laryngeal nerves reduces the risk of their injury during thyroid surgery

Abstract: Introduction: Even though incidence of recurrent laryngeal nerve palsy (RLNP) is low, it affects importantly the quality of life of patients and remains one of main medicolegal litigation problems in surgery. Intraoperative neuromonitoring (IONM) has become widely accepted tool helping in recurrent laryngeal nerve identification, however no clear association of IONM with RLNP rate has been demonstrated. The aim of our study was to assess whether training in IONM influences rates of RNLP after thyroid surgery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Previous studies have investigated the influence of neural signal changes on VCP during surgery 10 13 , as well as the influence of patients’ baseline conditions and postoperative pathological information on VCP 3 , 22 27 . Based on our clinical experience, we tested the hypothesis that low initial amplitude for V1 and R1 are associated with postoperative VCP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the influence of neural signal changes on VCP during surgery 10 13 , as well as the influence of patients’ baseline conditions and postoperative pathological information on VCP 3 , 22 27 . Based on our clinical experience, we tested the hypothesis that low initial amplitude for V1 and R1 are associated with postoperative VCP.…”
Section: Discussionmentioning
confidence: 99%
“…Another study comparing outcomes following thyroidectomies with and without standardized and routine use of IONM concluded that routine use of nerve monitoring allows less experienced surgeons to perform surgery safely with a similar RLN palsy rate as experienced surgeons [ 19 ]. Kuryga et al examined 2351 nerves at risk and showed that surgeons trained in IONM had a significantly lower rate of RLN palsy compared to surgeons who were not trained and do not routinely use IONM (0.58% vs. 2.8%, p < 0.01) [ 20 ]. In our study, in the cohort of patients who underwent surgery by surgeons who did not routinely use IONM, nerve monitoring was associated with prior neck surgery, suggesting that IONM was then used selectively for anticipated difficult dissections.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative nerve monitoring technology can effectively detect the relevant recurrent laryngeal nerve injury and effectively reduce the risk of recurrent laryngeal nerve injury during surgery. If intraoperative neuromonitoring has found damage to one RLN, it can effectively remind the surgeon to be more careful when dealing with the contralateral RLN to reduce the risk of bilateral RLN injury ( 37 , 38 ). More importantly, if the recurrent laryngeal nerve injury can be detected in time during the operation, the patient’s vital signs (such as respiratory indicators) can be detected more specifically, and the observation time can be extended, or hospitalization can be selected in the post-surgery period to reduce possible life-threatening risks.…”
Section: The Associated Complicationsmentioning
confidence: 99%